2021
DOI: 10.1073/pnas.2020382118
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide replacing or reducing chemotherapy in consolidation therapy for acute promyelocytic leukemia (APL2012 trial)

Abstract: As all-trans retinoic acid (ATRA) and arsenic trioxide (ATO) are widely accepted in treating acute promyelocytic leukemia (APL), deescalating toxicity becomes a research hotspot. Here, we evaluated whether chemotherapy could be replaced or reduced by ATO in APL patients at different risks. After achieving complete remission with ATRA-ATO–based induction therapy, patients were randomized (1:1) into ATO and non-ATO groups for consolidation: ATRA-ATO versus ATRA–anthracycline for low-/intermediate-risk patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 33 publications
2
57
0
Order By: Relevance
“…In addition, the CIR was higher in high-risk categories than that in intermediate-risk categories, and it had no statistical difference between intermediate-and low-risk categories in our study. Similar results were obtained in the APL2012 trial (35).…”
Section: Discussionsupporting
confidence: 87%
“…In addition, the CIR was higher in high-risk categories than that in intermediate-risk categories, and it had no statistical difference between intermediate-and low-risk categories in our study. Similar results were obtained in the APL2012 trial (35).…”
Section: Discussionsupporting
confidence: 87%
“…The initial results of the APL0406 trial (NCT00482833) showed that the combination of ATRA and ATO is at least not inferior to standard ATRA+chemotherapy in first-line therapy of low- or intermediate-risk APL [ 166 ]. Moreover, recent studies (APL2012 trial, NCT01987297) have demonstrated that the ATRA–ATO combination in both chemotherapy-replacing and -reducing settings in consolidation is effective as a traditional ATRA–chemo combination [ 17 ].…”
Section: Fusion Proteins As Transcriptional Modulatorsmentioning
confidence: 99%
“…First, the transcriptional modulators can synergize with conventional cytotoxic drugs in achieving antitumor efficacy with better tolerance, which is extremely important in children and elderly patients [ 11 , 12 ]. Second, targeting transcriptional machinery can prevent the establishment of drug resistance (NCT04017546, NCT01434316) [ 13 , 14 , 15 , 16 , 17 , 18 ]. Here, we review the fundamental aspects related to the design of tools for targeting gene transcription in hematological malignancies and analyze the current state-of-the-art in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely used in the treatment of various diseases including immune diseases [19,20] and has attracted more and more attention in recent years. The Chinese medicine arsenic being found to be effective in treating leukemia is one of the best examples [21]. Curcumin, an effective monomeric component mainly extracted from the traditional Chinese medicine turmeric, has been reported to have protective effects on SLE and ONFH [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%